Steady-state analysis of somatosensory evoked potentials - Noss, R S; Boles, C D; Yingling, C D (Electroencephalography and clinical neurophysiology, 1996)
We report the development of a new method for frequency domain analysis of steady-state somatosensory evoked potentials (SEPs) to amplitude-modulated electrical stimulation, which can be recorded in significantly less time than traditional SEPs. Resampling techniques were used to compare the steady-state SEP to traditional SEP recordings, which are based on signal averaging in the time domain of cortical responses to repetitive transient stimulation and take 1-2 min or more to obtain a satisfactory signal/noise ratio. Median nerves of 3 subjects were stimulated continuously with electrical alternating current at several modulation frequencies from 7 to 41 Hz. Amplitude modulation was used to concentrate the power in higher frequencies, away from the modulation frequency, to reduce the amount of stimulus artifact recorded. Data were tested for signal detectability in the frequency domain using the T(circ)2 statistic. A reliable steady-state response can be recorded from scalp electrodes overlying somatosensory cortex in only a few seconds. In contrast, no signal was statistically discriminable from noise in the transient SEP from as much as 20 s of data. This dramatic time savings accompanying steady-state somatosensory stimulation may prove useful for monitoring in the operating room or intensive care unit.We report the development of a new method for frequency domain analysis of steady-state somatosensory evoked potentials (SEPs) to amplitude-modulated electrical stimulation, which can be recorded in significantly less time than traditional SEPs. Resampling techniques were used to compare the steady-state SEP to traditional SEP recordings, which are based on signal averaging in the time domain of cortical responses to repetitive transient stimulation and take 1-2 min or more to obtain a satisfactory signal/noise ratio. Median nerves of 3 subjects were stimulated continuously with electrical alternating current at several modulation frequencies from 7 to 41 Hz. Amplitude modulation was used to concentrate the power in higher frequencies, away from the modulation frequency, to reduce the amount of stimulus artifact recorded. Data were tested for signal detectability in the frequency domain using the T(circ)2 statistic. A reliable steady-state response can be recorded from scalp electrodes overlying somatosensory cortex in only a few seconds. In contrast, no signal was statistically discriminable from noise in the transient SEP from as much as 20 s of data. This dramatic time savings accompanying steady-state somatosensory stimulation may prove useful for monitoring in the operating room or intensive care unit.